ANALYSIS OF REGIONAL FINANCIAL EFFECTIVENESS AND EFFICIENCY ON ECONOMIC GROWTH IN BOJONEGORO DISTRICT - Eka Yuliana Putri; Moehadi; Fahrizal Taufiqqurrachman (Jurnal Ekonomi, 2023)
This study aims to analyze the effectiveness and efficiency of regional finance in Bojonegoro Regency. This study uses three variables, namely, effectiveness, efficiency and economic growth. The data used in this study is secondary data sourced from the Ministry of Finance. The data includes revenue realization, revenue targets, expenditure targets and expenditure realization in Bojonegoro Regency during the 2011-2021 period. This study uses descriptive analysis with quantitative methods. The analytical tool used is table analysis, by comparing the ratio of target revenues/spending with actual receipts/spending. The results of the analysis show that the effectiveness of regional financial management in Bojonegoro Regency for 10 years has continued to increase with an average value that appears to be more than 100%, this shows that the local government can manage finances well. For the level of efficiency in financial management over the last 10 years it has not been efficient because the resulting ratio value is more than 60%, meaning that the resulting performance is less efficient and not good, the government in Bojonegoro Regency needs to improve its performance to achieve effective and efficient finance.